Report of a de novo c.2605C > T (p.Pro869Ser) change in the MED13L gene and review of the literature for MED13L-related intellectual disability - Zhi Yi; Ying Zhang; Zhenfeng Song; Hong Pan; Chengqing Yang; Fei Li; Jiao Xue; Zhenghai Qu (BMC, 2020)
Abstract Background MED13L-related intellectual disability is a new syndrome that is characterized by intellectual disability (ID), motor developmental delay, speech impairment, hypotonia and facial dysmorphism. Both the MED13L haploinsufficiency mutation and missense mutation were reported to be causative. It has also been reported that patients carrying missense mutations have more frequent epilepsy and show a more severe phenotype. Case presentation We report a child with ID, speech impairment, severe motor developmental delay, facial deformity, hypotonia, muscular atrophy, scoliosis, odontoprisis, abnormal electroencephalogram (EEG), and congenital ureteropelvic junction obstruction (UPJO) combined with high ureter attachment. We used whole-exome sequencing (WES) to detect the genetic aberration of the child and found a de novo mutation, c.2605C > T (p.Pro869Ser), in the MED13L gene. Neither of her parents carried the mutation. Additionally, we review the literature and summarize the phenotypes and features of reported missense mutations. After reviewing the literature, approximately 17 missense mutations in 20 patients have been reported thus far. For 18 patients (including our case) whose clinical manifestations were provided, 100% of the patients had ID or developmental delay (DD). A total of 88.9, 83.3 and 66.7% of the patients had speech impairment, delayed milestones and hypotonia, respectively. A total of 83.3% of the patients exhibited craniofacial deformity or other dysmorphic features. Behavioral difficulties and autistic features were observed in 55.6% of the patients. Cardiac anomalies were seen in only 27.8% of the patients. Of these patients, 44.4% had epileptic seizures. Of the 17 mutations, 2 were located in the N-terminal domain, 8 were located in the C-terminal domain, and 1 was located in an α-helical sequence stretch. One of them was located in the MID domain of the MedPIWI module. Conclusions We report a new patient with a reported missense mutation, c.2605C > T (p.Pro869Ser), who exhibited some infrequent manifestations except common phenotypes, which may broaden the known clinical spectrum. Additionally, by reviewing the literature, we also found that patients with missense mutations have a higher incidence of seizures, MRI abnormalities, autistic features and cardiac anomalies. They also have more severe ID and hypotonia. Our case further demonstrates that Pro869Ser is a hotspot mutation of the MED13L gene.